Physicochemical, microbiological, and microstructural changes in germinated wheat grain - Darigash Shaimerdenova; Aigul Omaraliyeva; Baltash Tarabayev; Zhanar Chakanova; Damira Iskakova; Gaini Sarbassova; Maigul Kizatova; Sandugash Anuarbekova (PLoS ONE, 2025)
This study investigates the physicochemical, microbiological, and microstructural changes in soft wheat grain during germination under varying moisture conditions: moderately dry, moist, and wet. Pre-harvest sprouting can severely compromise grain quality and usability; however, understanding germination-induced changes offers insights into potential utilization strategies. Physical parameters—including thousand-kernel weight, test weight, and falling number—showed strong correlation with germination time, decreasing by 8.2%, 22%, and 74%, respectively. Microstructural analyses using optical microscopy, scanning electron microscopy (SEM), and Raman spectroscopy revealed substantial degradation of starch granule morphology and kernel structure, with compact vitreous endosperm becoming porous and disorganized as germination progressed. To optimize germination conditions for technological application, a central composite design with three factors (moisture, temperature, and time) was employed, analyzed using Statgraphics Centurion 19. Response surface modeling identified optimal conditions for starch content (22% moisture, 31°C, 84 h), protein content (21% moisture, 30°C, 72 h), and minimal microbial contamination (14% moisture, 33°C, 8 h). These findings provide a foundation for processing germinated soft wheat grain into value-added products, even when exposed to unfavorable harvest conditions.